Mangrove areas, heavy metal (Pb) content in seawater and sediments in the Coastal Area of the Bireuen Fisheries Port - Azhar, Rossy; Husna, Asmaul; Ramadani, Cut Putri Rizqia; Irfannur, Irfannur; Nugrahawati, Anis; Izwar, Akmal; Akmal, Yusrizal (Arwana: Jurnal Ilmiah Program Studi Perairan, 2024)
Bireuen Regency has the potential for coastal ecosystem resources. There are two Fish Landing Sites (PPI) with very high activity, namely PPI Peudada and PPI Jangka. The high level of activity leads to concerns about pollution, one of which is the presence of lead (Pb) metal. This research aims to assess the characteristics of mangrove areas, seawater samples for heavy metals Pb, and sediments around the coastal fishing port area of Bireuen Regency. The study was conducted in 2024. Research was carried out at two sampling locations of the Fish Landing Sites (PPI), namely the Peudada Fishing Port and the Jangka Fishing Port using purposive sampling methods. At the BARISTAND (Aceh Research and Industrial Standardization Agency) laboratory, samples were analyzed using an AAS (Atomic Absorption Spectrophotometer). The Pb concentrations in seawater and sediment at first Location (Peudada) were <0.0003 mg/L and 2.60 mg/kg, respectively. At second Location (Jangka), the concentrations were <0.0003 mg/L and 1.78 mg/kg, respectively. Observational results indicate that Pb metal contamination in seawater and sediment at locations 1 and 2 is still below the threshold limit set of Ministry of Environment No. 51 in 2004 and RNO in 1981.